(untitled) - Ira Pohl (Redwood City, California, 1994)
The book presents a seamless transition to C++ by using Pascal constructs to build a knowledge og programming in C++. It begins by introducing readers to C the focuses on C++ as a better C. Using numerous exercises and frequent language comparisons, the book teaches concepts quickly and introduces the language's object-oriented features. Based on the proposed ANSI C++ Standard, the book covers the latest language features including detailed discussions of templates and exception handling
Keywords: c++ ( computer language program )